Faktor ibu dalam pemberian suplemen pada anak prasekolah - Ineka Andi Tabita; Toto Sudargo; Fatma Zuhrotun Nisa (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Most children already meet their daily nutrient needs through food intake. However, many of them still consume food supplement. Supplement use becomes popular, but the pattern of supplement provision amongst preschool children has never been investigated. As the supplement use increases, there is an increased risk of over consumption of several micronutrients. Objective: To evaluate the predictors of preschooler’s supplement intake related to mother’s socio-demographic and lifestyle characteristics and to compare dietary pattern and nutritional status of preschool children who consume and did not consume supplements.Method: This is an observational study with case control design. The subjects were preschool children enrolled at Bandar Lampung Kindergarten and their mothers. The case and control group consisted of 79 mothers, respectively. Sociodemographic information and frequency of dietary supplement consumption were collected via parental questionnaires, including a 24-hour food recall.Result: Most children consume multivitamin supplement once a day (65.45%).The most infl uential factor for mothers to give food supplement to their child is media exposure. Mothers from families with higher income, lower educated, consume supplement and highly motivated were signifi cantly more likely to give food supplement to their child than their counterparts. Excluding nutrient intake from supplement, there were no differences in nutrient intake between supplement consumers and non-consumers. There were also no differences in nutritional status between supplement consumers and non-consumers.Conclusion: The most infl uential factor for mothers to give supplement to their child is media exposure. There were no differences in nutritional status and nutrient intake between supplement consumers and non-consumers.